Novel genetic and neuropathological insights in neurogenic muscle weakness, ataxia, and retinitis pigmentosa (NARP). Issue 2 (August 2016) - Claeys, Kristl G.; Abicht, Angela; Häusler, Martin; Kleinle, Stephanie; Wiesmann, Martin; Schulz, Jörg B.; Horvath, Rita; Weis, Joachim
ABSTRACT: Introduction: Neurogenic muscle weakness, ataxia, and retinitis pigmentosa (NARP) is caused by m.8993T>G/C mutations in the mitochondrial adenosine triphosphate synthase subunit 6 gene ( MT‐ATP6 ). Traditionally, heteroplasmy levels between 70% and 90% lead to NARP, and >90% result in Leigh syndrome. Methods: In this study we report a 30‐year‐old man with NARP and m.8993T>G in MT‐ATP6 . Results: Although the patient carried the mutation in homoplasmic state in blood with similarly high levels in urine (94%) and buccal swab (92%), he presented with NARP and not the expected, more severe Leigh phenotype. The mutation could not be detected in any of the 3 analyzed tissues of the mother, indicating a large genetic shift between mother and offspring. Nerve biopsy revealed peculiar endoneurial Schwann cell nuclear accumulations, clusters of concentrically arranged Schwann cells devoid of myelinated axons, and degenerated mitochondria. Conclusions: We emphasize the phenotypic variability of the m.8993T>G MT‐ATP6 mutation and the need for caution in predictive counseling in such patients. Muscle Nerve 54 : 328–333, 2016